2016
DOI: 10.1186/s12915-016-0232-y
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin promotes exploitation in complex environments by accelerating decision-making

Abstract: BackgroundFast responses can provide a competitive advantage when resources are inhomogeneously distributed. The nematode Caenorhabditis elegans was shown to modulate locomotion on a lawn of bacterial food in serotonin (5-HT)-dependent manners. However, potential roles for serotonergic signaling in responding to food discovery are poorly understood.ResultsWe found that 5-HT signaling in C. elegans facilitates efficient exploitation in complex environments by mediating a rapid response upon encountering food. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 74 publications
(132 reference statements)
5
57
1
Order By: Relevance
“…While early experiments suggested that ADF may have a role in the detection of dauer pheromone [44], a role for the ADF neurons in sex pheromone attraction has not been previously described. In hermaphrodites, ADF is best known for its roles in detection of foodrelated compounds, release of serotonin, inhibition of entry into the dauer stage, and modulation of food-dependent behaviors [44,[67][68][69][70]. Our results indicate that, in males, ADF also detects ascr#3 (and perhaps other ascarosides), and that the transmission of this signal is independent of serotonin release.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…While early experiments suggested that ADF may have a role in the detection of dauer pheromone [44], a role for the ADF neurons in sex pheromone attraction has not been previously described. In hermaphrodites, ADF is best known for its roles in detection of foodrelated compounds, release of serotonin, inhibition of entry into the dauer stage, and modulation of food-dependent behaviors [44,[67][68][69][70]. Our results indicate that, in males, ADF also detects ascr#3 (and perhaps other ascarosides), and that the transmission of this signal is independent of serotonin release.…”
Section: Discussionmentioning
confidence: 64%
“…Here, we favor the idea that ascaroside detection by the male ADF differentially engages shared navigational circuits. Indeed, ADF activation is associated with locomotor slowing in hermaphrodites [68,70] (though ADF-derived serotonin is also implicated in promoting roaming [75]), and exposure to ascr#3-containing plates increases male reversal rate [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings, however, demonstrate a synergistic role for HSN and NSM in promoting a locomotion behavioral state known as dwelling, where worms inside a bacteria lawn move slowly and turn frequently to explore locally. This behavior relies on serotonin production in both the NSM and HSN neurons, but not in ADF 26,50 .…”
Section: Discussionmentioning
confidence: 97%
“…Alternative strategies for coping with heterogeneous environment have been proposed, for example, in bacteria and worms (32)(33)(34)(35). It is expected that the significance of resetting is diminished if changes to the environment are slow or smooth.…”
Section: Discussionmentioning
confidence: 99%